The Impact Of Lockdown On Early Childhood Emotional Development - Khassani Nur Amalinda; Melinda Virantika; Maiya Arisca (Universitas Muhammadiyah Ponorogo, 2021)
This study aims to improve the social and emotional development of early childhoodduring the pandemic. The Covid-19 pandemic has an effect on AUD playing activities.Children must stay at home so that they do not play socializing with their friends, so theapplication is carried out, namely collaboration between parents and teachers throughpositive habituation. This study used a descriptive qualitative research design with a casestudy approach. In this study, the writer wanted to explore learning problems through several journal sources, especially in the social emotional development carried out at home. From the results of the analysis, the researcher could get the results of the collaboration between parents and increase children's emotional social, namely parents or educators who have an important role in educating for children's growth and development. The implication of the application of daily habituation and teacher collaboration includes taking the processof child development through daily habituation and always paying attention to learning, making children enthusiastic, because parents have an important role in child development. Parents and teachers in conveying learning and taking good care by giving freedom to children can develop children's ideas or imaginations. The emotional development of children can be seen from their daily activities that are independent, responsible, and comfortable with their parents